2020
DOI: 10.1111/aos.14541
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and antiamoebic activity of dysprosium‐based nanoparticles using contact lenses as carriers against Acanthamoeba sp.

Abstract: Purpose Contact lenses have direct contact with the corneal surface and can induce sight‐threatening infection of the cornea known as Acanthamoeba keratitis. The objective of this study was to evaluate the dysprosium‐based nanoparticles (Dy‐based NPs), namely Fe3O4‐PEG‐Dy2O3 nanocomposites and Dy(OH)3 nanorods, as an active component against Acanthamoeba sp., as well as the possibility of their loading onto contact lenses as the drug administering vehicle to treat Acanthamoeba keratitis (AK). Methods The Dy‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Inorganic nanoparticles including metal nanoparticles have been incorporated in various medical applications due to their affordable production, versatility, low toxicity, and robustness [ 39 ]. When it comes to amoebae, several nanoparticles bearing antibiotics, namely silver- and gold-based nanocarriers have proved efficacious against amoebae [ 31 , 39 , 40 , 41 ] Other studies employed tannic acid-modified silver, azole, dysprosium-based, and cobalt phosphate nanoparticles and reported marked anti- Acanthamoebic activity [ 42 , 43 , 44 , 45 ]. Due to its potency against bacteria, the nanocarrier ZnO has been implemented in various biomedical applications including water treatment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic nanoparticles including metal nanoparticles have been incorporated in various medical applications due to their affordable production, versatility, low toxicity, and robustness [ 39 ]. When it comes to amoebae, several nanoparticles bearing antibiotics, namely silver- and gold-based nanocarriers have proved efficacious against amoebae [ 31 , 39 , 40 , 41 ] Other studies employed tannic acid-modified silver, azole, dysprosium-based, and cobalt phosphate nanoparticles and reported marked anti- Acanthamoebic activity [ 42 , 43 , 44 , 45 ]. Due to its potency against bacteria, the nanocarrier ZnO has been implemented in various biomedical applications including water treatment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies about the effects of gold nanoparticles on the loading and delivery of drugs in contact lenses have confirmed that gold nanoparticles can increase drug uptake from soaking solution and improved the release kinetics without affecting the critical properties of contact lenses for therapeutic application (Maulvi et al., 2019 ; Li et al., 2021b ). Drug-loaded nanocontact lenses have successfully achieved controlled and sustained drug delivery, which is a promising approach to treat ophthalmic diseases (Rodrigues et al., 2020 ; Khan et al., 2021 ; Kusrini et al., 2021 ; Liu et al., 2021 ; Maulvi et al., 2021 ; Li et al., 2021a ).…”
Section: Novel Methods For Preparing Drug-loaded Contact Lensesmentioning
confidence: 99%
“…Ocular penetration of topical drugs is limited by tears and the corneal epithelium barrier. Several recent studies continue to explore nanoemulsions, micelles, and hydrogels to improve drug retention and penetration [98][99][100][101][102][103][104][105][106]. Similarly, others have begun investigating the possibility of ultrasoundguided transcorneal delivery wherein cavitation of the corneal epithelium and increased temperature aids in penetration and absorption of hydrophilic molecules [107][108][109].…”
Section: Improving Drug Deliverymentioning
confidence: 99%